Congenital hyperinsulinism: diagnostic and management challenges in a developing country - case report - Cheri Mathews John; Prakash Agarwal; Suriyakumar Govindarajulu; Sandhya Sundaram; Senthil Senniappan (Korean Society of Pediatric Endocrinology, 2017)
Management of congenital hyperinsulinemia of infancy (CHI) is challenging. A 4-month-old female infant with persistent hypoglycemia and elevated insulin levels was diagnosed with CHI. Gallium-68 DOTANOC positron emission tomography/computed tomography (PET/CT) scan (68Ga-labeled [1,4,7,10-tetraazacyclododecane-N,N',N'',N'''-tetraacetic acid]-1-NaI3-octreotide) demonstrated focal disease in the body of the pancreas. Genetic studies indicated paternal inheritance, making focal disease likely. She was started on diazoxide therapy with partial improvement in blood glucose levels. Due to a suboptimal response to diazoxide and the likelihood of focal disease amenable to surgery, a laparoscopic subtotal pancreatectomy with preservation of the head of the pancreas was performed. The biopsy demonstrated diffuse hyperplastic pancreatic islet cells on immunohistochemistry, indicative of diffuse rather than focal disease. Paternal inheritance is a recognized indicator of focal disease. Gallium-68 DOTANOC PET/CT scan is the only available imaging modality in South India as 18F-L-dihydroxyphenylalanine (DOPA) PET/CT scan is not available at present. A laparoscopic approach reduces the postoperative recovery time and morbidity in such patients. The absence of 18F-L-DOPA PET/CT scan and the limited supply of diazoxide makes the management of this complex condition more challenging in developing countries.